Pengembangan Aplikasi Manajemen Informasi Magang Terowongan Angin Kecepatan Rendah Indonesia - Ivransa Zuhdi Pane (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2020)
An internship information management application at Indonesian Low Speed Wind Tunnel facility is useful for supporting managerial tasks related to internship activities, ranging from registration, task allocation, task implementation supervision to evaluation of the work results of the apprentices. This application is expected to not only support productivity and performance, but also provide input for management in making decisions related to the employment of apprentices in order to realize a synergy that has a positive impact on the smooth process of the wind tunnel test service business as a whole. To realize it, a software engineering activity by adopting prototyping methodology is carried out to build the application to be then operated in a desktop platform and be used as needed